Hubungan Antara Faktor Lingkungan Usaha Dengan Keberhasilan Kinerja Koperasi - Nailatul Khoiriyah C; Khoirun Nisa’ (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2021)
This research is descriptive research, while the method used is the survey method at the Tani Sadar cooperative and the Gunung Madu cooperative. In this study, 20 samples were used for each cooperative which were determined based on simple random sampling. Data analysis used descriptive analysis and analysis tables. The results in this study are as follows: 1) The condition of the business environment of the Tani Sadar cooperative and the Gunung Madu cooperative has a medium category 2) the successful performance of the Tani Sadar cooperative and the Gunung Madu cooperative has a category 3) there is a tendency of the relationship between the business environment and the successful performance. Suggestions that can be given regarding this research are: 1) the government and NGOs as facilitators, must support and develop cooperatives to be independent so that cooperatives do not always depend on facilitators. With the existence of independence, the cooperative will exist. 2) The management of the cooperative must often conduct counseling to its members, this is to create a sense of trust in the members of the cooperative so that members will participate more often in activities. 3) cooperatives must be more open to their members so that members will feel confident in the cooperative